Display Optimization for ICG Medical Imaging: A Subjective Evaluation Approach. (September 2014) - Flinn, Jeff T.; Miller, Amie; Saxe, Jonathan M.; Cao, Caroline G. L.
A medical imaging technique known as Indocyanine Green (ICG) fluorescence cholangiography can potentially improve safety and reduce cost in minimally invasive surgery, but is not widely used. Refinement of existing ICG imaging prototypes would facilitate more widespread use of the technology. The goal of this research was to optimize the display of an ICG imaging prototype, post-hoc. Images produced by the prototype were systematically manipulated by altering brightness and contrast levels, and corresponding changes in perceived image quality were measured. Results showed that perceived image quality increased when either brightness or contrast of the original image was increased by 10% and 20%, respectively. With high quality images, similar manipulations of brightness or contrast did not improve the perceived image quality, nor did they degrade the perceived image quality significantly. These adjustments are expected to increase the overall clinical utility of the prototype as the perceived quality of the images most in need of improvement was enhanced.